IMPLEMENTASI SAFE WORK PRACTICE (SWP) DAN HIRARCH DALAM PENGELOLAAN LIMBAH B3 - Lailal Gusri; Hagabean, M. Doli; Yanova, Shally; Nuklirullah, M. (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2025)
Industrial and operational activities in various sectors, such as manufacturing, oil, gas, mining, and healthcare, have the potential to generate hazardous and toxic waste (B3) that can contaminate the environment, endanger human health, and threaten occupational safety. The management of B3 waste, which includes collection, storage, transportation, and final processing, carries a high risk of accidents and exposure to hazardous materials. These risks are generally due to workers' lack of knowledge of safe work procedures, improper use of personal protective equipment (PPE), and the failure to implement optimal occupational safety standards. The purpose of this study was to analyze the effectiveness of Safe Work Practices (SWPs) using the Hazard Identification, Risk Assessment, and Risk Control (HIRAC) approach at each stage of B3 waste management, from generation, packaging, and storage to transportation. The methods used included field observation, data collection from company documents, and risk analysis based on probability and severity matrices. The study results indicate that the implementation of SWPs has been generally effective, characterized by a predominantly low to moderate risk level. Therefore, the implementation of SWPs plays an important role in minimizing potential hazards in B3 waste management, but it is necessary to strengthen operational discipline and optimize supporting facilities to improve occupational safety performance.